2006
DOI: 10.1080/15693430601049660
|View full text |Cite
|
Sign up to set email alerts
|

Trends in bio-hydrogen generation – A review

Abstract: This paper reviews the research work carried out in bio-hydrogen generation from a renewable source, namely biomass. Bio-hydrogen production has several advantages when compared to photoelectrochemical or thermo-chemical processes due to the low energy requirement and investment cost. Hydrogen seems to be the future energy carrier by the virtue of renewable. Bio-hydrogen production processes also involve the production of CO 2 . However, this CO 2 was released from biomass, in which it was recently taken up, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 140 publications
0
11
0
Order By: Relevance
“…Biochemical technologies for biohydrogen production [172][173][174][175][221][222][223] started to receive attention after the oil crisis in 1970s. [157] Notwithstanding the steadily increasing interest and R&D on solar fuels, no commercial applications exist so far.…”
Section: Biochemical Hydrogen Productionmentioning
confidence: 99%
“…Biochemical technologies for biohydrogen production [172][173][174][175][221][222][223] started to receive attention after the oil crisis in 1970s. [157] Notwithstanding the steadily increasing interest and R&D on solar fuels, no commercial applications exist so far.…”
Section: Biochemical Hydrogen Productionmentioning
confidence: 99%
“…Apart from Scenedesmus obliquust that was used by Gaffron and Rubin [137], green algae species including Chlamydomonas reinhardtii and Chlamydomonas moewusii have also proven useful [122,141,174]. Among these a maximum efficiency of hydrogen production has been observed in Chlamydomonas reinhardii.…”
Section: Direct Biophotolysismentioning
confidence: 99%
“…Hydrogen Generation by Water Splitting Some of the heterocystous cyanobacteria strains used for hydrogen evolution include Anabaena Azollae, Anabaena variabilis, Anabaena cylindrica, Nostoc muscorum, Nostoc spongiaeforme, and Westiellopsis prolifica [174]. In the early 1970s Beneman and coworkers demonstrated that hydrogen and oxygen could be produced simultaneously for several hours using Anabaena cylindrica in a nitrogen deficient atmosphere [183,184] by flowing inert gas.…”
Section: Indirect Biophotolysismentioning
confidence: 99%
“…Sequence analysis of the DGGE bands from 2 to 21 days showed that many of the predominant bands were affiliated with known fermentative bacteria, including the genera Trichococcus 17 bands #10 and 11 , Sporotalea 18 band #17 , Clostridium bands #8 and 19 and Klebsiella 19 bands #9 and 16 . These bacteria are known to produce hydrogen from fatty acids with VFA accumulation 20 . The other predominant bands were also affiliated with the genera Desulfovibrio band #1 , Azovibrio band #2 , Thiobacillus band #3 , Propionivibrio bands #4 and 5 , Enterobacter bands #12, 13, 14, 15, and 20 , and Pantoea band #18 .…”
Section: Quantitative Analysis Of Dechlorinating Bacteriamentioning
confidence: 99%